Inhibition of a Mycothiol biosynthetic enzyme and a detoxification enzyme as anti-tubercular drug targets - Marakalala, Mohlopheni Jackson (Division of Chemical Pathology, 2014)
Includes abstract. Includes bibliographical references (leaves 131-141).